Ruxolitinib in Patients With Chronic Active Epstein-Barr Virus Infection: A Retrospective, Single-Center Study - Song, Yue; Wang, Jingshi; Wang, Yini; Wang, Zhao (Frontiers in Pharmacology, 2021)
Background: Chronic active Epstein–Barr virus infection (CAEBV) is one of the EBV-positive T- or NK-cell lymphoproliferative diseases. There is no safe and effective treatment currently and the only proven curable therapy is allogeneic hematopoietic stem cell transplantation (allo-HSCT). The JAK1/2 inhibitor, Ruxolitinib, is now as a novel therapy in inflammatory disease, and hypercytokinaemia is an important feature of CAEBV. Method: All patients who suffered active CAEBV and treated with Ruxolitinib as compassionate use in our center from Sep 1 2017 and Apr 30 2019 were retrospectively analyzed. Results: In general, seven out of nine patients responded to Ruxolitinib. Six out of seven patients became afebrile within 48 hours. The AST/ALT level of three out of four patients decreased after Ruxolitinib treatment. Both of the patients with cytopenia recovered. No significant decrease in EBV-DNA copy number was observed (p=0.161). For those seven patients who responded to Ruxolitinib, the median continuing period in remission was 7.1 weeks (range, 3.4-101.0 weeks). Two patients achieved long-term stable remission with Ruxolitinib monotherapy. None of these patients discontinued Ruxolitinib due to the possible toxicity. Conclusion: Ruxolitinib is an effective and rather safe option for controlling the inflammatory symptoms of active CAEBV, especially in patients with CAEBV who have failed previous treatments or have relapsed. It can also play a promising role in improving the quality of daily life of patients, and successfully bridging to allo-HSCT.